Sucking habit and malocclusion in children: a literature review: Kebiasaan mengisap dan maloklusi pada anak: kajian literatur - Aulia Anindita Ainayyah; Rika Damayanti Syarif; Donald R. Nahusona; Mansjur Nasir (Makassar Dental Journal, 2021)
Malocclusion is an occlusion that deviates from normal conditions, there is irregularity tooth or incorrect placement of dental arches outside the normal curve. Malocclusion can be caused by various factors, such as sucking habit. Sucking habit is divided into nutritive sucking habit and non-nutritive sucking habit. This literature review is aimed to describe the roles of nutritive and non-nutritive sucking habit on malocclusion. Eleven articles were obtained through articles search engines such as Google Scho-lar and PubMed. From the literature search, it was found that breast feeding and bottle feeding do not cause malocclusion, but several studies stated that bottle feeding can cause malocclusion. Meanwhile, finger sucking and pacifying are considered to cause malocclusion. Nutritive sucking habit and non-nutritive sucking habit are also related, children who do not breastfeed di-rectly from their mother or breastfeed less than 6 months are more likely to use pacifier or suck their fingers.